Barriers and Possibilities of Implementation of Customer Relationship Management on Small and Medium Enterprises by Womenpreneurs - Heny Hendrayati; Rahmy Karimah Syahidah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2018)
In Indonesia, Customer Relationship Management (CRM) is commonly used by large companies. Small Medium Enterprises (SMEs) are managed traditionally despite the growing amount of transactions. The growth of SMEs in Indonesia is not supported by CRM expertise. This study aims to analyze the implementation of CRM at the level of SMEs in the field of fashion managed by womenpreneurs in West Java. This research uses a descriptive method. The unit of analysis in this study was womenpreneurs engaged in fashion industry in West Java; 200 womenpreneurs were recruited using proportional random sampling. The results reveals that technology-based CRM is the most difficult to develop in construct. CRM by womenpreneurs does not use information technology, but it emphasizes on people and the process. Developing technology-based CRM is the best way to facilitate womenpreneurs in expanding their business.